2023
DOI: 10.5334/gh.1192
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rheumatic Process in Left and Right Ventricular Function in Patients with Mitral Regurgitation

Abstract: Background: Mitral regurgitation (MR) burdens the left and right ventricles with a volume or pressure overload that leads to a series of compensatory adaptations that eventually lead to ventricular dysfunction, and it is well known that in rheumatic heart disease (RHD) that the inflammatory process not only occurs in the valve but also involves the myocardial and pericardial layers. However, whether the inflammatory process in rheumatic MR is associated with ventricular function besides hemodynamic changes is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…Interestingly, although not correlated with the outcome, the LVEF in our RHD group was significantly lower than in our non-RHD group. The same finding was also reported by Rudiktyo et al [33], suggesting that besides the chronic load of the left ventricle, there could be another mechanism that worsens the LV function in patients with rheumatic MR. Other studies reported that the intrinsic myocardial process in RHD may play a role in the mechanism of this impaired LV contractility, as shown in the cardiac MRI and strain echocardiography [34,35]. Reduced LV and RV function, older age, more complex valve lesions, and a high AF proportion suggested that most of our patients presented in their late stages.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, although not correlated with the outcome, the LVEF in our RHD group was significantly lower than in our non-RHD group. The same finding was also reported by Rudiktyo et al [33], suggesting that besides the chronic load of the left ventricle, there could be another mechanism that worsens the LV function in patients with rheumatic MR. Other studies reported that the intrinsic myocardial process in RHD may play a role in the mechanism of this impaired LV contractility, as shown in the cardiac MRI and strain echocardiography [34,35]. Reduced LV and RV function, older age, more complex valve lesions, and a high AF proportion suggested that most of our patients presented in their late stages.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the echocardiographic findings, nearly one-fifth of the study participants (18.3%) have severely reduced left ventricular systolic dysfunction; the mean LVSd was 54.4±8.3mm; this study resembles a study by Rudiktyo et al, where the patients have a mean of 56.63 ± 8.57mm. 26 This study discovered that the mean left ventricular posterior wall end diastole and end systole (LVPWd) was found to be 10.01±1.18mm. This finding is higher than a study conducted in Multan, Pakistan, where the mean LVPWd was reported as 7.13 ± 1.95mm 27 and another study by Meel et al from South Africa also reported a mean LVPWd of 8.5 ± 1.5mm.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the echocardiographic findings, nearly one-fifth of the study participants (18.3%) have severely reduced left ventricular systolic dysfunction; the mean LVSd was 54.4±8.3mm; this study resembles a study by Rudiktyo et al, where the patients have a mean of 56.63 ± 8.57mm. 26 …”
Section: Discussionmentioning
confidence: 99%